2019
DOI: 10.1021/acs.accounts.8b00559
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophanes as Platforms for Reactive Multimetallic Complexes

Abstract: Multimetallic cofactors supported by weak-field donors frequently function as reaction centers in metalloproteins, and many of these cofactors catalyze small molecule activation (e.g., N 2 , O 2 , CO 2) with prominent roles in geochemical element cycles or detoxification. Notable examples include the iron-molybdenum cofactor of the molybdenum-dependent nitrogenases, which catalyze N 2 fixation, and the NiFe 4 S 4 cluster and the Mo(O)SCu site in various carbon monoxide dehydrogenases. The prevailing proposed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…[12,13] The same holds true for the Al-C bond lengths [1.958(1)-1.975(2) Å] and the C-Al-C bond angles [113.22 5-118.52(7)°] of the Al(CH 3 ) 2 group, whose values are comparable to those observed for the mononuclear counterparts. Solid state structures (hydrogen atoms are omitted for the sake of clarity) with selected bond lengths /Å and angles /°of (a) IIb: Al1-Al1' 6.482(1), Al1-N1 1.918(1), Al1-N2 1.907(1), Al1-C18 1.969(2), Al1-C19 1.975(2), N1-Al1-N2 96.71(6), C18-Al1-C19 113.96 (9); (b) IIc: Al1-Al2 7.3823(4), Al1-N1 1.904(1), Al1-N2 1.915(1), Al2-N3 1.912(1), Al2-N4 1.911(1), Al1-C18 1.963(2), Al1-C19 1.974(2), Al2-C28 1.968(1), Al2-C29 1.967(1), N1-Al1-N2 95.02 5 8, Al1-N1 1.923(1), Al1-N2 1.927(1), Al1-C18 1.958(1), Al1-C19 1.973(1), N1-Al1-N2 95.14(4), C18-Al1-C19 115.14(6); (b) IIi: Al1-Al1' 7.396(1), Al1-N1 1.930(1), Al1-N2 1.9193(9), Al1-C18 1.970(1), Al1-C19 1.967(1),N1-Al1-N2 95.23(4), C18-Al1-C19 113.22 (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] The same holds true for the Al-C bond lengths [1.958(1)-1.975(2) Å] and the C-Al-C bond angles [113.22 5-118.52(7)°] of the Al(CH 3 ) 2 group, whose values are comparable to those observed for the mononuclear counterparts. Solid state structures (hydrogen atoms are omitted for the sake of clarity) with selected bond lengths /Å and angles /°of (a) IIb: Al1-Al1' 6.482(1), Al1-N1 1.918(1), Al1-N2 1.907(1), Al1-C18 1.969(2), Al1-C19 1.975(2), N1-Al1-N2 96.71(6), C18-Al1-C19 113.96 (9); (b) IIc: Al1-Al2 7.3823(4), Al1-N1 1.904(1), Al1-N2 1.915(1), Al2-N3 1.912(1), Al2-N4 1.911(1), Al1-C18 1.963(2), Al1-C19 1.974(2), Al2-C28 1.968(1), Al2-C29 1.967(1), N1-Al1-N2 95.02 5 8, Al1-N1 1.923(1), Al1-N2 1.927(1), Al1-C18 1.958(1), Al1-C19 1.973(1), N1-Al1-N2 95.14(4), C18-Al1-C19 115.14(6); (b) IIi: Al1-Al1' 7.396(1), Al1-N1 1.930(1), Al1-N2 1.9193(9), Al1-C18 1.970(1), Al1-C19 1.967(1),N1-Al1-N2 95.23(4), C18-Al1-C19 113.22 (5).…”
Section: Resultsmentioning
confidence: 99%
“…[3] However, it has been shown that β-di- ketiminates do not necessarily behave as spectator ligands and their (hidden) non-innocence is an interesting feature in terms of reactivity. [3,4] Poly(β-diketiminate)s have been recently emerged as useful tools in coordination chemistry, [5] and the respective bis(β-diketiminate)s grant access to both, mono- [6] and polynuclear complexes, [7] not only depending on the respective element and the experimental protocol, but also on the ligand framework. In this regard, three types of bis(β-diketimine)s have to be considered: (i) nitrogen-bridged, (ii) backbone-bridged, and (iii) macrocyclic derivatives (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Coupling between the metal binding site and another metal(s) can also increase the density of electronic states available for a multi-electron transformation. Bimetallic and multi-metallic EAM catalysts have been used for CO2 reduction ( Figure 5B), (58,99) cycloadditions ( Figure 5D) 60…”
Section: Molecular Catalysismentioning
confidence: 99%
“…In many enzymes, two or more metal centers in the active site are able to activate both nucleophilic and electrophilic reactants, leading to improved kinetics and higher selectivity. Researchers have proven that dual/multiple activation catalysts can accomplish higher efficiencies than conventional monofunctional catalysts in terms of reactivity, substrate selectivity and, potentially, cost-efficiency [ 15 , 16 , 17 , 18 , 19 ]. For bimetallic or trimetallic catalysts, well-designed ligands with low molecular weight could fully fulfill the cooperative interaction between metals [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%